Advantages of simultaneous radial nerve and tendon reconstruction - a case report - Kempný, Tomáš; Votruba, Tomáš; Xani, Z; Ramadani, F; Lipový, Břetislav; Dvořák, Zdeněk; Holoubek, Jakub; Bartková, Julia (Acta chirurgiae plasticae (English ed.), 2023)
Transection of the radial nerve is frequently associated with humeral shaft fractures that are part of a very complex upper extremity injury. In the presented case, a 19-year-old man with a 10-cm radial nerve defect with a need for nerve grafting to recover complete sensory and motor deficit of the radial nerve. In our case, at the same time we provided the tendon transfer of musculus (m.) pronator teres to m. extensor carpi radialis brevis, m. flexor carpi ulnaris to m. extensor digitorum communis, m. palmaris longus to m. extensor pollicis longus, and long sural nerve graft because of an extensive zone of the injury. The assumption was that if these two procedures are performed in one surgery, it will accelerate overall recovery, restore the functionality of the upper limb more quickly, and thus enable a faster recovery.
Keywords: nervus radialis; Transplantation, Autologous; Humans; přenos šlachy; Neurosurgical Procedures; mladý dospělý; Humeral Fractures; autologní transplantace; výsledek terapie; lidé; fraktury humeru; Tendon Transfer; horní končetina; kosterní svaly; Male; Sural Nerve; Treatment Outcome; Muscle, Skeletal; Upper Extremity; Radial Nerve; Young Adult; nervus suralis; mužské pohlaví; neurochirurgické výkony